1989
DOI: 10.1246/cl.1989.611
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Environment around the Metal Center Observed by the Epoxidation with the Iron Complexes of Bleomycin and the Synthetic Analogue

Abstract: cis-β-Methylstyrene is oxidized either with the Fe(III)–H2O2 or with the Fe(II)–O2 complex systems of bleomycin and the synthetic model ligand PYML-6 to give optically active epoxide, showing that the environment around the iron-nucleus is chiral enough to cause asymmetric epoxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The above three reports [226,234,235] were the only precedents known for significant asymmetric epoxidation using hydrogen peroxide and a synthetic nonheme iron complex catalyst when the first breakthrough and promising result was reported in 2007. [236] After developing an efficient procedure for the racemic epoxidation of aromatic alkenes, [237,238] an extensive screen of a large number of commercially available chiral amines was undertaken to explore the possibility of an asymmetric version.…”
Section: Hydrogen Peroxide As the Oxygen Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…The above three reports [226,234,235] were the only precedents known for significant asymmetric epoxidation using hydrogen peroxide and a synthetic nonheme iron complex catalyst when the first breakthrough and promising result was reported in 2007. [236] After developing an efficient procedure for the racemic epoxidation of aromatic alkenes, [237,238] an extensive screen of a large number of commercially available chiral amines was undertaken to explore the possibility of an asymmetric version.…”
Section: Hydrogen Peroxide As the Oxygen Sourcementioning
confidence: 99%
“…[28] Thus, catalysts based on Ti, [231] Pt [232] and Ru [233] have been reported for asymmetric epoxidations of olefins using hydrogen peroxide. [16] An early attempt for asymmetric epoxidation by a synthetic non-heme Fe catalyst and hydrogen peroxide was reported simultaneously with the aerobic epoxidation using N1 [226] (Table 6, vide supra). [16] An early attempt for asymmetric epoxidation by a synthetic non-heme Fe catalyst and hydrogen peroxide was reported simultaneously with the aerobic epoxidation using N1 [226] (Table 6, vide supra).…”
Section: Hydrogen Peroxide As the Oxygen Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Ohno et al reported that the Fe(III) complex of a pyridine model ligand-6 (PYML-6) of bleomycin catalyzes epoxidation of some olefins using aqueous hydrogen peroxide. Although enantioselectivity and yield are modest, the report is interesting in terms of development of asymmetric oxidation catalysis of abundant iron [27].…”
Section: Metal-catalyzed Asymmetric Epoxidation Of Unfunctionalized Omentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27] Highly enantioselective epoxidation of difficult substrates such as ,-disubstituted aromatic enones and -alkyl styrenes, not accessible by other methods, have also been described. 23,24 However, a major limitation still resides at the fact that iron catalyzed asymmetric epoxidations have been limited in scope to olefins conjugated to aromatic rings, [19][20][21][22]23,[24][25][26][27][28][29][30][31][32][33][34][35] and remains to be accomplished for aliphatic substrates. Particularly interesting are cyclic aliphatic enones.…”
mentioning
confidence: 99%